Zulkarnain dalam Nilai-Nilai Peradaban Islam di Dunia Pendidikan Islam - Oktariani Dahana, Eva (Journal of Comprehensive Science, 2024)
Islamic education plays a crucial role in shaping a generation that is not only intellectually intelligent but also morally upright. This study aims to examine the Islamic civilizational values found in the story of Zulkarnain and how these values can be applied in Islamic education. The method used is library research, analyzing various relevant sources of literature. The results of the study indicate a gap between the educational theory that emphasizes moral and spiritual values and its implementation in everyday educational practice. The story of Zulkarnain offers guidance on leadership based on faith, justice, and wisdom, which is highly relevant for application in education. Additionally, the broader concept of jihad, encompassing moral and intellectual struggle, is also highlighted in this study. This research recommends integrating these values into the Islamic education curriculum to strengthen students' character, foster a balance between knowledge and faith, and promote social awareness. By applying the values derived from the story of Zulkarnain, Islamic education is expected to produce a generation capable of facing the challenges of the times with moral integrity and a spirit of positive contribution to society.